2020
DOI: 10.1103/physrevresearch.2.013011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement incompatibility and steering are necessary and sufficient for operational contextuality

Abstract: Contextuality is a signature of operational nonclassicality in the outcome statistics of an experiment. This notion of nonclassicality applies to a breadth of physical phenomena. Here, we establish its relation to two fundamental nonclassical entities in quantum theory; measurement incompatibility and steering. We show that each is necessary and sufficient the failure of operational contextuality. We exploit the established connection to contextuality to provide a novel approach to problems in measurement inco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 56 publications
2
38
1
Order By: Relevance
“…Specifically, contextuality provides an advantage to the maximum copying fidelity. Our result directly links contextuality to a quantum advantage [5,12,13].…”
mentioning
confidence: 61%
“…Specifically, contextuality provides an advantage to the maximum copying fidelity. Our result directly links contextuality to a quantum advantage [5,12,13].…”
mentioning
confidence: 61%
“…It is important to notice that whenever two measurements are compatible, they cannot be used to produce quantum advantage in tasks like Bell nonlocality [5] or Einstein-Podolsky-Rosen steering [6,7]. Moreover, it was recently shown that joint measurability is equivalent to a specific notion of classicality, namely, preparation non-contextuality [8,9]. Hence, one may think of compatible measurements as 'classical' , and incompatible measurements as a resource for the above tasks.…”
mentioning
confidence: 99%
“…Note here that, obliviousness in an operational theory can equivalently be represented as the obliviousness at the level of ontic states if the ontological model of that operational theory is preparation non-contextual [17]. In this connection, it is also worthwhile to note that, in two-input-two-output Bell scenario the preparation non-contextuality assumption in an ontological model of quantum theory can also be viewed as locality condition [28,29]. We may call it as trivial preparation non-contextuality condition.…”
Section: Introductionmentioning
confidence: 99%